2022
DOI: 10.21608/ejhc.2022.226561
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Massage by Using Lavender and Chamomile Oils of Intact Skin on Outcomes of Moderately Burned Patients

Abstract: Background: Burn injury is considered as one of the most painful types of trauma that a patient can experience. Pain management is an integral component of nursing practice. Attention has been paid to the use of complementary and alternative therapies as non-pharmacological methods for reducing patient's pain and anxiety. Aim of the study: to assess the effect of massage by using lavender and chamomile oils of intact skin on pain and anxiety of moderately burned patients. Research design: A quasi-experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 1 publication
(1 reference statement)
0
1
0
Order By: Relevance
“…Surya et al (2020) discovered that lavender and rose aromatherapy can reduce pain in postoperative patients. Another study showed that aromatherapy massage with lavender and chamomile oils can reduce and control pain in burn patients (M Gallo et al, 2022).…”
Section: Aromatherapy-based Interventionmentioning
confidence: 99%
“…Surya et al (2020) discovered that lavender and rose aromatherapy can reduce pain in postoperative patients. Another study showed that aromatherapy massage with lavender and chamomile oils can reduce and control pain in burn patients (M Gallo et al, 2022).…”
Section: Aromatherapy-based Interventionmentioning
confidence: 99%